Knowledge of heatlh effects of dietary fiber among nurses and the general population in croatia: comparative analysis - Ljubicic, Marija (2017)
INTRODUCTION: Nurses play diverse roles in educating patients about healthy diet and in promoting healthy eating habits, through their conversations with patients and families and through their work providing enteral and parenteral feeding to critically ill patients. Given the position of nurses as key providers of dietary guidance, and given the health benefits of dietary fibre, we wanted to assess the level of fibre-related knowledge among nurses in Croatia. OBJECTIVES: The primary objective of this cross sectional study was to compare knowledge between nurses and general population from Croatia about the health importance of consuming dietary fibre. METHODS: Knowledge of 369 nurses and 727 residents from the general population about fibre was assessed using a validated survey developed by the CI&DETS Polytechnic Institute, Viseu, Portugal. Differences between nurses and general population were assessed for significance using the Mann-Whitney U test and Kruskal-Wallis test, while associations between study variables and knowledge were explored using Spearman rank correlation coefficients. RESULTS: The level of knowledge among nurses and the general population in Croatia about dietary fibre varies from «undecided» to «partial knowledge». No association was observed between nurse education level and either general knowledge about fibre or knowledge about the health benefits of fibre intake. No significant differences were observed between nurses and general population in general knowledge (p = 0.894) or in health-related knowledge (p = 0.578). CONCLUSION: Results suggest the need for updating and expanding nursing curricula. The similar level of knowledge between nurses and the general population about dietary fibre indicates the need to strengthen nurse education and training in the areas of diet and diet therapy in Croatia. Given the role of nurse as diet educators and advisors, this may help improve the quality of health care.